Use of hedges to omoimasu to soften speech and its implications for Japanese politeness teaching - Winingsih, Irma; Santoso, Budi; Wahyuningsih, Tri Mulyani (Universitas Dian Nuswantoro, 2021)
In Japanese society, the main concept in communicating is to consider the other person's feelings by not speaking directly, too frankly or to the point. One of the grammatical features this concept is Verb omoimasu which means in English I think (I think…, I think….). In the result of the essays by the students who take the Japanese Popular Writing course. In his essay students should use these verbs which also function as hedges to express opinions or ideas but ignore them because they may not understand that the use of these functional verbs is to maintain language politeness, especially in communicating in Japanese. Seeing this phenomenon, the writers tried to find out by identifying student essays that do not use these hedges, and the possible causes. Then by adopting the concept of communicating in Japanese that considers the feelings of the other person, the writers have found out how the implications of using these hedges have on the values of politeness in language that have effect on the politeness of behavior of students who take Japanese Popular Article Writing lectures. With research that adopts the concept of communicating in Japanese society, the writers can create a language politeness learning model that is expected to influence behavioral aspects.